Patient feedback on medical students in tertiary health care: are medical students accepted in clinical practice? - Rubliauskas, Kasparas; Šalkauskaitė, Aistė; Macas, Andrius (Acta medica Lituanica, 2019)
Background. Clinical teaching is central in the training of medical students. Although medical studies without practice are hard to imagine nowadays, for most patients this type of learning is still difficult to understand and not always acceptable. Materials and methods. A prospective anonymous survey of 150 participants was carried out. Participants were patients at the Surgery Department of the Kauno Klinikos Hospital of the Lithuanian University of Health Sciences. The questionnaire comprised 12 questions: the first two on the patients’ personal information and the rest about the patients’ opinion about medical students. Statistical analysis software IBM SPSS Statistics 23.0 was used for statistical data analysis. A statistically significant difference was observed when p < 0.05. Results. Seventy-eight per cent of patients would allow medical students to be present during their surgery; 78.7% would permit medical students help the anaesthetic team with procedures; 79% responded that students were not introduced, and 21.3% stated that they were informed about students’ involvement for learning purposes. The majority of the respondents (62%) answered that the main advantage was additional practical skills. Talking about disadvantages, 25% of the respondents thought that students were not professional enough, 6% were worried about an overcrowded operating theatre, yet the majority of patients (69%) did not worry about this. Conclusions. The majority of patients would agree with the involvement of medical students in their surgical operations and induction of anaesthesia. The patients pointed out that the general reason for their concern over surgical operations was that the students were not professional enough and did not have required skills. Most patients thought that involving students in their surgical operations did not have negative influence on surgery quality.